2019
DOI: 10.1002/htj.21577
|View full text |Cite
|
Sign up to set email alerts
|

Physical aspects on unsteady MHD‐free convective stagnation point flow of micropolar fluid over a stretching surface

Abstract: The unsteady magnetohydrodynamic (MHD) stagnation point flow of micropolar fluid across a vertical stretching surface with second-order velocity slip is the main concern of the present paper. The influence of electrical energy, temperature-dependent thermal conductivity, thermal radiation, Joule heating, and heat sink/source is investigated. The basic partial differential equations are changed into ordinary differential equations with the help of appropriate similarity variables and then solved by the fourth-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Non-Newtonian flows are very important in many disciplines [9][10][11][12][13][14]. Blood exhibit non-Newtonian characteristics including shear-thinning and viscoelasticity, but in this study, we will focus on the shear-thinning behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Non-Newtonian flows are very important in many disciplines [9][10][11][12][13][14]. Blood exhibit non-Newtonian characteristics including shear-thinning and viscoelasticity, but in this study, we will focus on the shear-thinning behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…More interesting works with various geometries and physical constraints are recently being done on Newtonian and non-Newtonian convective fluid/nanofluid boundary layer flows by eminent researchers in Refs. [12][13][14][15][16][17][18].…”
Section: Background Informationmentioning
confidence: 99%
“…They used slandering heated surface to know the behavior considering effects along with viscous dissipation. Anantha Kumar et al [ 18 ] observed rheology of micropolar fluid along with stagnation point and magnetic field. They used second-order (velocity slip) of considered flow model past a heated vertical surface.…”
Section: Introductionmentioning
confidence: 99%